Handbook of erosion modelling - Morgan, R. P. C. (Royston Philip Charles), 1942-; Nearing, M. A. (Mark A.); Wiley InterScience (Online service) (Chichester, West Sussex, UK ; Hoboken, N.J. : Wiley, 2011)
The movement of sediment and associated pollutants over the landscape and into water bodies is of increasing concern with respect to pollution control, prevention of muddy floods and environmental protection. In addition, the loss of soil on site has implications for declining agriculturalproductivity, loss of biodiversity and decreased amenity and landscape value. The fate of sediment and the conservation of soil are important issues for land managers and decision-makers. In developing appropriate policies and solutions, managers and researchers are making greater use of erosion models to cha.
Front Matter -- Colour Plates -- Introduction / R P C Morgan -- Model Development. Model Development: A User's Perspective / R P C Morgan -- Calibration of Erosion Models / V G Jetten, M P Maneta -- Dealing with Uncertainty in Erosion Model Predictions / K J Beven, R E Brazier -- A Case Study of Uncertainty: Applying GLUE to EUROSEM / J N Quinton, T Krueger, J Freer, R E Brazier, G S Bilotta -- Scaling Soil Erosion Models in Space and Time / R E Brazier, C J Hutton, A J Parsons, J Wainwright -- Misapplications and Misconceptions of Erosion Models / G Govers -- Model Applications. Universal Soil Loss Equation and Revised Universal Soil Loss Equation / K G Renard, D C Yoder, D T Lightle, S M Dabney -- Application of WEPP to Sustainable Management of a SmallCatchment in South west Missouri, US, Under Present Land Use and with Climatic Change / J M Laflen -- Predicting Soil Loss and Runoff from Forest Roads and Seasonal Cropping Systems in Brazil Using WEPP / A J T Guerra, A Soares da Silva -- Use of GUEST Technology to Parameterize a Physically-Based Model for Assessing Soil Erodibility and Evaluating Conservation Practices in Tropical Steeplands / C W Rose, B Yu, R K Misra, K Coughlan, B Fentie -- Evaluating Effects of Soil and Water Management and Land Use Change on the Loess Plateau of China using LISEM / R Hessel, V G Jetten, B Liu, Y Qiu -- Modelling the Role of Vegetated Buffer Strips in Reducing Transfer of Sediment from Land to Watercourses / J H Duzant, R P C Morgan, G A Wood, L K Deeks -- Predicting Impacts of Land Use and Climate Change on Erosion and Sediment Yield in River Basins Using SHETRAN / J C Bathurst -- Modelling Impacts of Climatic Change: Case Studies using the New Generation of Erosion Models / J P Nunes, M A Nearing -- Risk-Based Erosion Assessment: Application to Forest Watershed Management and Planning / W J Elliot, P R Robichaud -- The Future Role of Information Technology in Erosion Modelling / D P Guertin, D C Goodrich -- Applications of Long-Term Erosion and Landscape Evolution Models / G R Willgoose, G R Hancock -- Gully Erosion: Procedures to Adopt When Modelling Soil Erosion in Landscapes Affected by Gullying / J W A Poesen, D B Torri, T Vanwalleghem -- Future Developments. The Future of Soil Erosion Modelling / M A Nearing, P B Hairsine -- Index.
Includes bibliographical references and index.
Print version record.
Keywords: Soil erosion -- Simulation methods; TECHNOLOGY & ENGINEERING -- Agriculture -- General; Soil erosion -- Simulation methods; Aufsatzsammlung; Bodenerosion; Mathematische Modellierung; Aufsatzsammlung; Bodenerosion; Mathematische Modellierung; Electronic books